Off label use of a 7Fr endo-biliary forceps system for endovascular inferior vena cava biopsy - Stavros Grigoriadis; Stavros Spiliopoulos; Athanasios Korogiannos; Konstantinos Palialexis; Dimitrios Filippiadis; Nikolaos Kelekis (CVIR Endovascular)
Abstract Endovascular inferior vena cava (IVC) mass biopsy emerges as a minimally invasive promising technique for the acquisition of tissue samples for histological analysis, crucial for determining the malignant or benign nature of the lesion and guiding subsequent treatment. This report details the first successful off label use of a low-profile 5.2Fr biliary forceps system, via a 7Fr sheath, for endovascular IVC biopsy in a 61-year-old male patient with a history of left nephrectomy due to Gravitz tumour presenting with IVC thrombosis at 5-years follow up, suspicious for recurrence.